From Symbolic to Substantive ESG: A Systematic Literature Review on Digital Transformation, Dynamic Capabilities, Transformational Leadership, and Organizational Performance - Haryanto, Tri; Rahayu, Agus; Adi Wibowo, Lili (Riviera Publishing, 2026)
The increasing importance of Environmental, Social, and Governance (ESG) practices and digital transformation has raised interest in their role in improving organizational performance. However, prior studies show inconsistent results, particularly regarding whether these initiatives directly enhance performance or depend on internal and contextual factors. This research aims to systematically review the literature on the relationship between ESG strategies, digital transformation, and organizational performance, with particular attention to the mediating roles of dynamic capabilities and innovation, the enabling role of transformational leadership, and the moderating influence of institutional context. Using a Systematic Literature Review (SLR) based on PRISMA guidelines, this study analyzed 72 peer-reviewed journal articles published between 2010 and 2024 from Scopus and Web of Science. The findings show that ESG and digital transformation do not consistently produce direct performance gains. Instead, their effects depend on organizations’ ability to build dynamic capabilities, foster innovation, and adapt strategically. Transformational leadership strengthens organizational learning and change readiness, while institutional quality can either support or constrain performance outcomes. This review proposes an integrative conceptual framework grounded in the Resource-Based View, dynamic capability theory, stakeholder theory, institutional theory, and transformational leadership theory. The study concludes that organizational performance is more likely to improve when ESG and digital transformation are implemented substantively, supported by strong capabilities, leadership, and institutional quality.